The effect of WO42– group in xerogels doped with Ln2–xPrx(WO4)3 where Ln = La, Gd - Grobelna, Beata; Bojarski, Piotr (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
We present a synthesis of highly efficient xerogels doped with Ln 2–x Prx(WO4)3, where Ln = La or Gd as novel phosphors. For comparison, the synthesis of xerogels doped only with Pr(III) and La(III) ions was made. The photoluminescence properties of Pr(III) ions in xerogels were studied by means of luminescence spectroscopy. In particular, an efficient energy transfer from WO42– to Pr(III) ions was observed and demonstrated by their enhanced luminescence intensity. Especially interesting seems to be strong red acceptor emission observed upon excitation at 240 nm (donor excitation). Therefore, 4f–4f emission makes the system usable for red phosphor applications. Additionally, the emission intensity of the materials was improved by reducing concentration of such quenchers as water molecules and OH groups by the thermal treatment.
Optica Applicata, Vol. 40, 2010, nr 2, s. 359-366
Keywords: sol-gel method; optyka; photoluminescence; praseodymium(III) ions; energy transfer process